Analisis Kinerja Tata Kelola Teknologi Informasi Menggunakan Framework Cobit 2019 Pada Universitas Muhammadiyah Jambi - Marthiawati, Noneng; Kurniawansyah, Kevin; Aryani, Reni (STMIK Sinar Nusantara, 2024)
An educational institution, Muhammadiyah Jambi University has integrated IT into its operational processes. Muhammadiyah Jambi University's information technology has not adjusted its governance system to achieve the greatest possible benefits from IT use and to keep advancing corporate IT governance. Consequently, in order to ensure that the corporate IT governance system at Muhammadiyah University Jambi is in line with business objectives, an IT governance plan is required. IT governance is an important asset for measuring the effectiveness and efficiency of improving a company's business processes using information technology. This study explains the way of a company can create specialized governance solutions for corporate information technology (IT) by analyzing IT governance performance using Cobit 2019 framework. The aim of this research is to analyze the performance of a system properly and provide recommendations for improving information technology governance at Muhammadiyah University Jambi. The methods are both qualitative by conducting observations, interviews, and taking work documents and quantitative methods by filling out questionnaires in 2019 Cobit design tool. The results of this research show several important processes that must be a top priority in the company, namely BAI06 (Managed IT Changes), DSS01 (Managed Operations), BAI07 (Managed IT Change Acceptance and Transitioning), BAI03 (Managed Solutions Identification & Build), DSS02 (Managed Service Requests & Incidents).